Late-Onset Concurrent Infection of Vaccine Strain VZV and HSV-1 after Varicella Vaccination in a Child with Natural killer T Cell Deficiency - Kutlu, Nurettin O; Karabey, Mehmet; Alacam, Sema; Tinastepe, Tuba; Yalcin, Suleyman; Aydogmus, Cigdem; Karabulut, Nuran (Journal of Pediatric Infectious Diseases, 2024)
We describe a case with natural killer cell deficiency of late-onset Oka vaccine varicella zoster virus (VZV) strain and Herpes simplex virus-1 (HSV-1) dual infection resulting in fatal clinical course. An 18-month-old boy presented with a papulovesicular rash, mucocutaneous candidiasis, encephalopathy, and severe respiratory distress 6 months after receiving varicella vaccine. VZV and HSV-1 were analysed by real-time reverse-transcriptase polymerase chain reaction (RT-qPCR) and Oka vaccine strain of VZV by gene sequencing. HSV-1 and VZV dual infection was detected in the blood and skin samples by RT-qPCR. Gene sequencing of VZV isolated from vesicular lesions was compatible with the Oka vaccine strain. Flow cytometry revealed a natural killer deficiency, but whole exome analysis failed to identify an associated genetic defect. Vesicular rashes in immunocompromised patients who were inadvertently vaccinated should be taken seriously, and antiviral therapy should be prompt and aggressive.
Keywords: varicella zoster virus; vaccine strain VZV; HSV-1; natural killer T cell deficiency